Esprit de corps: The Uses and Abuses of Shakespeare in Renaissance Man - Bényei, Tamás (FOCUS: Papers in English Literary and Cultural Studies, 2024)
"One recognizes the superiority o f the Greek man and the Renaissance man—but one would like to have them without the causes and conditions that made them possible." —Nietzsche, The Will to Power 882 The ending of Hamlet brings the advent of soldiers and the triumph of the military ethos in more than one sense: as the soldier Fortinbras takes over, reestablishing a sense of normality in the Danish court, he insists on giving the dead prince a military burial, thereby retrospectively transforming his story into one of heroism.